A Study of Photocatalysis of Methylene Blue of TiO2 Fabricated by Electric Spark Discharge Method. (8th October 2017) - Tseng, Kuo-Hsiung; Chung, Meng-Yun; Chang, Chaur-Yang; Cheng, Ting-Shou
Abstract : This study used the Electric Spark Discharge Method (ESDM) to prepare nano-Ti colloid. The results showed that the process efficiency increased according to the current and selecting different discharge periods (T O N -T O F F ). The preparation process is pollution-free and very contributive to using TiO2 for photocatalytic reaction to degrade organic compounds. This study used 99.9% pure Ti metal to examine the effects of different discharge parameter settings on the photocatalysis of methylene blue. The experimental results showed that the discharge period (T O N -T O F F ) has an effect on the characteristics of the prepared nano-Ti colloid but affects its concentration. The nano-Ti colloid, as prepared under different parameters, has poor photocatalytic reaction with methylene blue at the concentration of 50 mg/L. The nano-Ti colloid does not have favorable effect on degrading methylene blue above 50 mg/L. For degrading methylene blue at a low concentration of 10 mg/L, the 100-100 nano-Ti parameter is preferable. For degrading methylene blue at a high concentration of 30 mg/L, nano-Ti colloid with T O N exceeding 100 and T O F F fixed at 100 is better. As the nano-Ti colloid prepared by ESDM was free of chemical agents, when TiO2 was used in photocatalytic reaction to degrade organic compounds, there was no secondary pollution to the environment.